Quantifying population contact patterns in the United States during the COVID-19 pandemic - Dennis M. Feehan (Nature Portfolio, 2021)
Physical distancing measures have been widely adopted to reduce the spread of COVID-19. This study quantifies changes in interpersonal contact patterns in the US and finds an 82% reduction in contacts during early lockdowns in March and steady increases thereafter.